Metastatic Melanoma Presenting as Intussusception in an 80-Year-Old Man: A Case Report - Sarah Alghamdi; Yumna Omarzai (Case Reports in Pathology)
Malignant melanoma of the gastrointestinal tract is an uncommon neoplasm that could be primary or metastatic. Small intestine represents the most common site for the metastatic melanoma; however, it could be found anywhere in the gastrointestinal tract. Intussusception is a rare cause of intestinal obstruction in adults compared to children. In 90% of the cases, the underlying cause can be found, and in 65% of the cases, intussusception is caused by the neoplastic process. The majority of the neoplasms are benign, and about 15% are malignant. Metastatic melanoma is one of the most common metastatic malignancies to the gastrointestinal tract; however, the premortem diagnosis is rarely made. Here, we report an uncommon clinical presentation of metastatic melanoma causing intussusception in an 80-year-old man. This diagnosis should be considered in a differential diagnosis in any patient who presents with gastrointestinal symptoms and a history of melanoma.